Оптимальне керування режимами медикаментозної терапії та фізіотерапії в задачі реконструкції кісткової тканини - Martsenyuk, V. P.; Vakulenko, D. V.; Andrushchak, I. Ye. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2011)
The problem of building the drug therapy and physiotherapy models is presented as a problem of an optimal control with state limits for the model of reconstruction of bone tissue. The model includes the follocoing factors: population of osteocytes, osteoblasts and the density of the matrix. This approach has been numerically implemented using VisSim software.